Caribbean Regional Electricity Supply Options : Toward Greater Security, Renewables and Resilience - Gerner, Franz; Hansen, Megan (World Bank, 2012)
The Caribbean region continues to be plagued by high and volatile fuel prices, with limited economies of scale or diversity in electricity supply. Although several studies have examined alternative resource options for the region, they often only consider solutions for individual countries in isolation. When one looks at the Caribbean, however, it is apparent that the short distances between islands and market sizes present opportunities to benefit from regional solutions. Indeed, increasing interconnection in the Caribbean could pave the way for greater energy security, a larger use of renewable and enhanced climate resilience. The idea of regional interconnections is not new: gas pipelines are widely used to interconnect gas supply with gas demand, and electricity market interconnections have become the norm around the world. However, this option does not appear to have received the attention it merits in the specific context of the Caribbean. While this study analyzes a small subset of the imaginable regional energy options for the Caribbean, it shows that regional solutions warrant further study. This synthesis report builds from the technical report that the World Bank commissioned from Nexant, entitled-Caribbean regional electricity generation, interconnection, and fuels supply strategy. It analyzes a range of regional options. Although further analysis is required, the hope is that this synthesis report will help to fuel the conversation about interconnected development pathways for the Caribbean.